The State of the Global Clean and Improved Cooking Sector - Putti, Venkata Ramana (World Bank, Washington, DC, 2015)
The global clean and improved cooking solutions sector has evolved significantly in recent years. Clean and improved cooking solutions are also beginning to generate attractive market opportunities for local and international private enterprises in the provision of cooking appliances, fuels, and financing. This report covers all clean and improved cooking solutions that can improve on the fuel efficiency and emissions performance of traditional cooking technologies such as the three stone fire, open U-shaped clay or mud stoves, metal bucket charcoal stoves, and unvented coal stoves. Under the definition of improved cooking solutions the report includes all cook stoves that improve fuel efficiency without reducing particulate matter emissions to the low levels necessary for optimal health and environmental outcomes as defined by World Health Organization (WHO) household air pollution guidelines and the International Standards Organization International Workshop Agreement (ISO IWA) guidelines for improved cook stoves. The objectives of this report are threefold: (1) establish a common fact base for sector analysis; (2) build a case for increased sector focus and investment; and (3) inform intervention strategies. The information provided in this report constitutes a best-effort attempt to harmonize definitions and data sources to give a comprehensive picture of the overall sector landscape, with the caveat that this is likely to be somewhat imprecise in various instances because of these definitional and data quality challenges. This report is divided into the following chapters: chapter one gives introduction. Chapter two presents the case for clean and improved cooking; chapter three presents the demand for clean and improved cooking energy; chapter four deals with the supply landscape; chapter five deals with the cooking appliance supply chain; chapter six presents the sector ecosystem; and chapter seven presents’ recommendations.